Cerebrovascular Compliance Within the Rigid Confines of the Skull - Zamir, Mair; Moir, M. Erin; Klassen, Stephen A.; Balestrini, Christopher S.; Shoemaker, J. Kevin (Frontiers in Physiology, 2018)
Pulsatile blood flow is generally mediated by the compliance of blood vessels whereby they distend locally and momentarily to accommodate the passage of the pressure wave. This freedom of the blood vessels to exercise their compliance may be suppressed within the confines of the rigid skull. The effect of this on the mechanics of pulsatile blood flow within the cerebral circulation is not known, and the situation is compounded by experimental access difficulties. We present an approach which we have developed to overcome these difficulties in a study of the mechanics of pulsatile cerebrovascular blood flow. The main finding is that while the innate compliance of cerebral vessels is indeed suppressed within the confines of the skull, this is compensated somewhat by compliance provided by other ”extravascular” elements within the skull. The net result is what we have termed “intracranial compliance”, which we argue is more pertinent to the mechanics of pulsatile cerebral blood flow than is Intracranial Pressure.